INTEGRATION OF NAQLI AND AQLI KNOWLEDGE IN ISLAMIC SCIENCE UNIVERSITY OF MALAYSIA: CONCEPT AND MODEL - Zarkasih Zarkasih; Kadar M Yusuf; H. Hasanuddin; Susilawati Susilawati (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
The aim of this study is to explore the concepts and models of integration implemented by Islamic Science University of Malaysia (USIM). USIM was chosen as the focus of this study because of its firm commitment to the implementation of integration. For instance, the USIM vision statement makes it clear that the university has an ambition to become a “leader in the integration of naqli and aqli knowledge”. The method of data collection used in this study involved the analysis of document and interviews. Documentation was used to obtain data related to integration concepts and models applied in USIM. Then, interviews were conducted to gather information from key informant to supplement the findings from the documentation. It was found that the integration concepts and models applied at USIM consist of four categories or levels namely: al-nusus (ayatization), al-muqaranah (comparison), al-taqyim (adaptation) and at-tafaqquh (integration). These four concepts were have been implemented in detail in the learning process, as well as in research and community development.